2017
DOI: 10.1007/s00264-017-3639-3
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and cardiorespiratory complications in trochanteric femoral fractures: a ten year retrospective analysis

Abstract: This study identified high patient age, distinctive comorbidities, male sex, and high osteoporosis grade as significant risk factors for increased in-hospital mortality in the treatment of trochanteric femoral fractures. Furthermore, high ASA grade and a liberal transfusion regime led to an increased incidence of cardio-respiratory complications. Patient-specific characteristics, especially osteoporosis grade and pre-existing medical conditions, may assist in the identification of high-risk patients and allow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 40 publications
3
23
0
1
Order By: Relevance
“…A liberal blood transfusion may result in pro-inflammatory, immunomodulating, and prothrombotic effects [37], which could cause serious systemic complications, such as cardiovascular events. Carow J et al [38] reported that a liberal blood transfusion causes higher cardiorespiratory complications in patients with trochanteric femoral fractures. We believe that the prediction of Hb drop would be helpful when blood transfusion is being considered in such fragile patients.…”
Section: Discussionmentioning
confidence: 99%
“…A liberal blood transfusion may result in pro-inflammatory, immunomodulating, and prothrombotic effects [37], which could cause serious systemic complications, such as cardiovascular events. Carow J et al [38] reported that a liberal blood transfusion causes higher cardiorespiratory complications in patients with trochanteric femoral fractures. We believe that the prediction of Hb drop would be helpful when blood transfusion is being considered in such fragile patients.…”
Section: Discussionmentioning
confidence: 99%
“…A number of variables were collected based on literature and availability [6,8,10,11]. The following pre-operative baseline variables were collected upon admission to the ED: age, sex, Body Mass Index/ Quetelet index (BMI), living situation prior to admission (at home, at home with home care, institutional care facility, other), whether or not the patient was living with a partner, number of different comorbidities (as mentioned in admission form), number of different medications, whether patients had experienced a previous episode of delirium, cognitive impairment (as mentioned in the admittance form, either declined or not declined), use of oral anticoagulants (yes/no), hemoglobin-(mmol/L), creatinine-(µmol/L), C-reactive protein (mg/L) levels.…”
Section: Measurementsmentioning
confidence: 99%
“…Patients aged 85 years or above constitute the fastest growing age group and are at even higher risk for postoperative complications and death than the general geriatric population [4][5][6][7]. These geriatric fracture patients are a distinct age group with considerable risk of negative medical outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recognised that such patients are a vulnerable group who suffer multiple medical co-morbidities, which impact on morbidity and mortality [2,3]. …”
Section: Introductionmentioning
confidence: 99%